A Concise History of Ancient Israel : From the Beginnings Through the Hellenistic Era - Schipper, Bernd U. (Critical Studies in the Hebrew Bible, 2021)
The history of biblical Israel, as it is told in the Hebrew Bible, differs substantially from the history of ancient Israel as it can be reconstructed using ancient Near Eastern texts and archaeological evidence. In A Concise History of Ancient Israel, Bernd U. Schipper uses this evidence to present a critical revision of the history of Israel and Judah from the late second millennium BCE to the beginning of the Roman period. Considering archaeological material as well as biblical and extrabiblical texts, Schipper argues that the history of "Israel" in the preexilic period took place mostly in the hinterland of the Levant and should be understood in the context of the Neo-Assyrian expansion. He demonstrates that events in the exilic and postexilic periods also played out differently than they are recounted in the biblical books of Ezra and Nehemiah. In contrast to previous scholarship, which focused heavily on Israel's origins and the monarchic period, Schipper's history gives equal attention to the Persian and early Hellenistic periods, providing confirmation that a wide variety of forms of YHWH religion existed in the Persian period and persisted into the Hellenistic age.Original and innovative, this brief history provides a new outline of the historical development of ancient Israel that will appeal to students, scholars, and lay readers who desire a concise overview.